Laboratory and on ice tests to evaluate kinematics of Para ice hockey players - Rosso, V.; Cinus, G.; Gastaldi, L. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2020)
Sprint and technique abilities of Para ice hockey players are of great importance to increase skating performance. To assess skating abilities, kinematics is widely used. This study had two purposes: (1) to assess two-dimensional kinematics of Para ice hockey players` performance in the laboratory and on ice (sprint and agility) tests and (2) to quantify the relationship between the laboratory and on ice performance. Seven athletes were recruited. In the laboratory, three alternated reach tests were performed in which athletes touched the ground as many times as possible with hands, elbows, or shoulders. The sprint test consisted of 30-m skating at the highest speed starting from standstill, whereas the agility test consisted of sprinting for four left curves and four right curves. Athletes` movements in the laboratory and on ice tests were acquired using a portable technology. In the laboratory, the best performance was realized when participants touched the ground with hand or elbow. In the sprint test, lower speed and trunk inclination were observed in the first 10 m. In the agility test, greater blade angle was observed in the left curves, compared with the right curves. Significant correlations were found between the laboratory and on ice test performance. Overall, these findings are a useful indicator of athletes` skating abilities and could be used to increase athletes` ability to accelerate rapidly and improve sledge manoeuvrability. For detailed player information, kinematics should still be evaluated using sport specific tests and video analysis.